Wizerunek Polki w twórczości Мariny Cwietajewej. - Mazurek, Halina (Acta Polono-Ruthenica, 2009)
Cvetaeva was always intrugued with her Polish roots. She had no chance of meeting her mothers moher so she used her poetic imagination to create her grandmothers portrait in her poetry. Personal characteristics such as: extraordinary beauty, pride, self-restraint rebellious facial expression or secret of life are fund in Polish female characters in Her works (e.g. princess Izabela Czartoryska, Marina Mnishek). Mnishek is the most complex and controversial personality. Out of contrariness so typical of Cvetaeva, while creating the Mnisheks image the poetess focused on positive characteristics and opposed stereotypes connected with this character, which always characterised artistic expression of the poetess. Another feature of her poetry was identification with her female characters and creation of imaginary, usually ideal life attitudes.